presentation of research as Front Cover in the journal: Inorganic Chemistry, 2024, 63, 7, 3229–3249 - Drouza, Chryssoula (My University, 2026)
Honorary presentation of my work for its innovation, published under title "Experimental and Theoretical Investigation of the Mechanism of the Reduction of O2 from Air to O22– by VIVO2+–N,N,N-Amidate Compounds and Their Potential Use in Fuel Cells"
Keywords: Natural sciences